(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This study provides a comprehensive analysis of antigen-independent T-lymphocyte maturation in the thymus at molecular, cellular, and systemic levels. The research focuses on the differentiation stages of lymphoid progenitor cells, the genetic recombination of T-cell receptors (TCR), and the mechanisms of positive and negative selection that ensure immune tolerance. The findings indicate that thymic maturation is a highly regulated and selective process, in which approximately 95–98% of developing T-lymphocytes undergo apoptosis during selection. Only functionally competent and self-tolerant T-cells are allowed to enter peripheral circulation. The study also highlights the critical role of thymic microenvironment components, including epithelial and dendritic cells, in maintaining selection accuracy. In addition, age-related thymic involution was shown to significantly reduce the production of naïve T-cells, thereby affecting immune responsiveness. Statistical and comparative analyses confirm that disruptions in thymic selection mechanisms may lead to immunodeficiency and autoimmune disorders. Overall, the results emphasize the essential role of antigen-independent immunogenesis in establishing central immune tolerance and maintaining immune system stability, providing a theoretical basis for further research in clinical immunology and immunopathology.